2019
DOI: 10.1186/s41043-019-0161-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of medication adherence between type 2 diabetes mellitus patients who pay for their medications and those who receive it free: a rural Asian experience

Abstract: BackgroundTreatment plans fail if patients have poor medication adherence. Our aim was to compare medication adherence, reasons for non-adherence, and satisfaction with community support among type 2 diabetes mellitus patients who pay for their medications and those who receive it free.MethodsA descriptive cross-sectional study was conducted at Anuradhapura, Sri Lanka, among patients who were on oral anti-diabetic drugs for at least 3 months. They were grouped into two: universal-free group and fee-paying grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…While medication nonadherence is a universal issue, the burden of medication cost on the patient may vary in other countries due to different health care system models being utilized (e.g., universal health care system vs. subsidized vs. mixed). [54][55][56][57] Additionally, drug prices in the United States are high due to lack of regulation or negotiation about prices of new prescription medications introduced into the market, whereas other countries employ methods to control drug pricing. 58 Despite these variations, even patients being cared for within a different health care system model may experience medication cost barriers and, as a result, experience poor outcomes; thus, research on what tools clinicians practicing in those areas would desire to help minimize cost barriers at point of prescribing would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…While medication nonadherence is a universal issue, the burden of medication cost on the patient may vary in other countries due to different health care system models being utilized (e.g., universal health care system vs. subsidized vs. mixed). [54][55][56][57] Additionally, drug prices in the United States are high due to lack of regulation or negotiation about prices of new prescription medications introduced into the market, whereas other countries employ methods to control drug pricing. 58 Despite these variations, even patients being cared for within a different health care system model may experience medication cost barriers and, as a result, experience poor outcomes; thus, research on what tools clinicians practicing in those areas would desire to help minimize cost barriers at point of prescribing would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere in an Asian study researchers noted that willingness to avoid side effects were common reasons of nonadherence. 41 In Iran, Benrazavy and Khalooei's study showed that education level was the most important predicting factor of adherence to medication. 10…”
Section: Patient Characteristic Factorsmentioning
confidence: 99%
“…42 Similar trends were noted in a study in Sudan 39 and Asia. 41 Not surprisingly, treatment adherence becomes more challenging when the treatment itself is perceived as more difficult, onerous, or burdensome. 13 In Iran it was found that non-adherence among patients with T2DM was influenced by lack of a deep understanding of the medical knowledge on diabetes in many aspects, and those who had little faith in doctors' prescriptions and recommendations.…”
Section: Health System Factorsmentioning
confidence: 99%
“…The study by Rathish et al from a rural province in Sri Lanka makes an important contribution to the sparse literature on the subject in the country and establishes the benefits of government-funded universal free-health services in enhancing medication coverage and adherence in low-income diabetes patients [3]. However, there are certain concerns regarding the study methodology and interpretation that are discussed below.…”
mentioning
confidence: 99%
“…A study in Brazil also observed a high-rate of clinical inertia during diabetes care [8]. The Rathish et al [3] study had reported the lack of availability of some anti-diabetes agents like DPP-4 inhibitors in the free service compared to the paid service which could have significant implications on patient glycemic status. Future studies from the region should therefore evaluate the potential interconnectedness of adherence, glycemic control, and clinical inertia in their settings.…”
mentioning
confidence: 99%